Treatment of A First Unprovoked Seizure - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The Quality Standards Subcommittee of the AAN and Practice Committee of the CNS have reviewed published literature to determine when to begin treatment after a first unprovoked seizure, risk of recurrence, prevention of recurrence, development of chronic epilepsy, and side effects of AEDs.